Effect of the full coverage policy of essential medicines on medication adherence: A quasi-experimental study in Taizhou, China - Guo, Zhigang; He, Zixuan; Li, Huangqianyu; Zheng, Liguang; Shi, Luwen; Guan, Xiaodong (Frontiers in Public Health, 2022)
Objective Different forms of full coverage policy of essential medicines (FCPEMs) have been adopted worldwide to lower medication expenditure and improve adherence. This study aims to analyse the effect of FCPEMs on patients' medication adherence in Taizhou city, China. Methods This study was a quasi-experimental study and set treatment and control groups. We extracted Electronic Health Records (EHRs) for hypertension and diabetes 1 year before and after FCPEMs implementation and their medication adherence level assessed by physicians. We applied the propensity score matching (PSM) method to balance the bias between the two groups. Then, the descriptive analysis was used to compare the differences in the reported medication adherence. Using the Difference-In-Differences (DIDs) method, the fixed-effect model with the logistic regression was built to analyse the effects of FCPEMs. Results 225,081 eligible patients were identified from the original database. In the baseline year, FCPEM covered 39,251 patients. After PSM, 6,587 patients in the treatment group and 10,672 patients in the control group remained. We found that the proportion of patients with high adherence in the treatment group increased by 9.1% (60.8 to 69.9%, P < 0.001) and that in the control group increased by 2.6% (62.5 to 65.2%, P < 0.001). The regression results showed that FCPEMs significantly increased patients' medication adherence (OR = 2.546, P < 0.001). Conclusion FCPEMs significantly improved medication adherence. Socially disadvantaged individuals might benefit more from continuing FCPEM efforts. Expanding the coverage of FCPEMs to other medicines commonly used in patients with chronic diseases may be a promising strategy to manage chronic diseases and promote patient outcomes.